The influence of firm characteristics and macroeconomic factors on financial performance: Evidence from the Portuguese hotel industry - Fernanda Matias; Sandra Rebelo; Georgette Andraz; José Guerreiro (Economies, 2024)
This study examines the determinants of the financial performance of the Portuguese hotel industry. Despite the economic relevance of the hotel industry and financial performance as an indicator of business survival, academic research on the factors that influence it in the context of this industry, particularly in Portugal, is not extensive. This study encompassed a sample of 738 hotel companies from 2016 to 2021, using data from the Orbis database. This research was based on the assumption that a company's size, liquidity, the tangibility of its assets, and debt level influence financial performance in the hotel industry, as well as the assumption that gross domestic product and consumer sentiment also affect the business success of hotel companies. By applying a panel data methodology, the findings indicate that all variables showed significant influence on financial performance, except liquidity. The analysis also reveals that smaller companies were more negatively affected by the demand decline induced by the COVID-19 pandemic. To improve the financial performance of the Portuguese hotel industry, the findings suggest that policymakers must work towards ensuring diversified sources of financing for the hotel business, such as investment subsidies, so that companies can minimize debt, especially during periods of slow economic growth. Additionally, companies must promote management strategies that enhance self-financing. Both measures could help companies increase their size, taking advantage of good business opportunities to explore economies of scale.
Keywords: 330; financial performance; performance determinants; hotel industry; panel regression; Portugal